Multi-objective optimization of an ORC power plant using one-dimensional design of a radial-inflow turbine with backswept rotor blades. (15th December 2021) - Jankowski, Marcin; Klonowicz, Piotr; Borsukiewicz, Aleksandra
Abstract: Organic Rankine cycle (ORC) power plants are a promising technology for converting low and medium temperature energy sources into electricity. In order to fully exploit the potential of an ORC, the components of the system should be designed appropriately. One of the key elements of the ORC installation, substantially affecting the system efficiency, is a turboexpander. This study concerns a multi-objective optimization of an ORC coupled with a one-dimensional radial-inflow turbine (RIT) model. Particular attention is given to determination of optimal parameters which have an impact on the turbine geometry of the nozzle and the rotor. The nozzle pitch to chord ratio and the blade angle at the rotor inlet are investigated as one of the decision variables. The first parameter is rarely discussed in most studies and it is either a fixed value or its optimum is determined using correlations developed for axial-flow turbines. Applying the blade angle as a variable is associated with the use of backswept rotor blades, which is achievable in the ORC and results in higher turbine efficiency. By means of Non-dominated Sorting Genetic Algorithm-II (NSGA-II) and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS), the optimal design point has been determined. It was found that by applying the blade angle at the rotor inlet as the decision variable, the optimal blade sweep design featuring a 0.00% incidence enthalpy loss can be obtained. Based on the parametric analysis, it was reported that by making wrong design choices with respect to the RIT decision variables, the turbine efficiency may be decreased by almost 8.00%, leading to a decrease in the net power output by more than 8.00% and an increase in the electricity production cost of more than 7.00%. Highlights: Model of a radial-inflow turbine (RIT) with backswept rotor blades is developed. Multi-objective optimization of an ORC coupled with a RIT model is conducted. An optimal blade sweep design featuring a zero-incidence loss is obtained. Wrong design choices leading to decrease in a turbine efficiency by 7.43% are noted. An optimal sweep angle decreases with an increase in the turbine specific speed.